Developing Students’ Participation in a Mixed-levels Reading Class via Cooperative Integrated Reading and Composition (CIRC) - Sulistianingsih, Endang (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2018)
Students, especially at the higher level need to bean efficient reader to comprehend somereading materials from varied sources associated with their studies. Teaching reading becomes not easy sincethe teacher has to face the problems on how to teach reading in a mixed-levelsreading class? How can all students become motivated more active in reading class? How to promote cooperation among students with divergent competency and motivation? To address such questions, this paper demonstrates how reading skill, participation, and cooperation can be developed through CIRC. The research was a case study where quantitative and qualitative were mixed. The participants of this research were students of communication studies at the Social and Political Science Faculty in higher education. Eighteen students participated in this research. The participant was took using saturation sampling. The data was collected through observation to determine students’ participation and reading comprehension test to measure the student’s reading comprehension level.CIRCwas used as teaching instruction during the intervention. Through this method, learning reading can increase good interrelationship, individual and group responsibility, interpersonal and small group skills. Therefore, a presence of cooperation is established, comprehension can be developed, and passive students become active while active students become active. This research is useful for EFL teacher who teaches in a big class where his/her studentshave different levels of reading proficiency.